Gambaran makroskopik dan mikroskopik ureter pada hewan coba postmortem - Savalina, Dinda N.S.; Ticoalu, Shane H.R.; Wangko, Sunny (e-Biomedik, 2016)
Abstract: Postmortem changes provide a lot of valuable information about the time, causes, and mechanisms of death. This study was aimed to obtain an overview of the macroscopic and microscopic postmortem changes of ureter at several time intervals during 48 hours postmortem. This was a descriptive study using pigs as samples. The results showed that macroscopic postmortem changes of ureters began to appear at 5 hours postmortem marked by changes in color, consistency, and length of the ureters. Meanwhile, the microscopic postmortem changes of the ureters began to appear at 4 hours postmortem characterized by congestion, however, the transitional epithelial cell could be identified. At 5 hours postmortem, a number of transitional cells showed pycnotic nuclei. At 15 hous postmortem, the transitional layer began to detach from the lamina propria; cells with pycnotic nuclei increased in number. At 30 hours postmortem, the transitional layer was detached from the lamina propria and in general the structure of ureter layers could not be identified. Conclusion: Macroscopic changes in color, consistency and length of ureter could be observed the earliest at 5 hours postmortem Microscopic changes could be identified at 4 hours postmortem characterized by congestion, however, the transitional cells could be idemtified. At 5 hours postmortem, the early necrosis of transitional cells occured. At 30 hours postmortem the structure of ureter layers could not be identified.Keywords: macroscopic and microscopic description, ureter, postmortem.Â Abstrak: Perubahan postmortem banyak memberikan informasi baik mengenai waktu, penyebab, maupun mekanisme kematian. Penelitian ini bertujuan untuk mendapatkan gambaran makroskopik dan mikroskopik ureter postmortem berdasarkan variasi waktu sampai 48 jam postmortem. Jenis penelitian ialah deskriptif dengan menggunakan babi sebagai hewan coba. Hasil penelitian menunjukkan perubahan makroskopik ureter hewan coba, mulai tampak pada 5 jam postmortem ditandai dengan perubahan warna, konsistensi dan panjang ureter sampai 30 jam postmortem. Perubahan mikroskopik ureter hewan coba postmortem mulai tampak pada 4 jam postmortem ditandai dengan adanya kongesti, sel epitel transisional masih dapat diidentifikasi. Pada 5 jam postmortem sebagian inti sel transisional tampak piknotik. Pada 15 jam postmortem sebagian lapisan epitel transisional telah terlepas dari lamina propia dan sel-sel dengan inti piknotik makin jelas. Pada 30 jam postmortem lapisan epitel transisional dengan inti sel piknotik telah terlepas dari lamina propria dan secara keseluruhan struktur lapisan ureter telah sulit diidentifikasi. Simpulan: Perubahan makroskopik mulai terlihat pada 5 jam postmortem ditandai dengan perubahan warna, konsistensi, dan panjang ureter. Perubahan mikroskopik dapat diidentifikasi pada 4 jam postmortem ditandai adanya kongesti, pada 5 jam postmortem dimulainya nekrosis sel epitel transisional, dan pada 30 jam struktur lapisan ureter telah sulit diidentifikasi.Kata kunci: gambaran makroskopik dan mikroskopik, ureter, postmortem